Chromatin and chromatin remodeling enzymes. - Allis, C. David; Wu, Carl (Methods in enzymology, 2004)
DNA in the nucleus of plant and animal cells is stored in the form of chromatin. Chromatin and the Chromatin remodellng enzymes play an important role in gene transcription. *Histone Bioinformatics *Biochemistry of histones, nucleosomes and chromatin *Molecular cytology of chromatin functions.